Impact of adiposity on clinical outcomes in people living with a Fontan circulation. (15th April 2021) - Cao, Jacob Y.; Tran, Derek; Briody, Julie; Attard, Chantal; Hassan, Ebrahim Bani; Simm, Peter; Burchill, Luke; Twigg, Stephen M.; Fiatarone-Singh, Maria A.; Ayer, Julian; Celermajer, David S.; d'Udekem, Yves; et al.
Abstract: Background: To assess the association between body composition and the risk of adverse outcomes in Fontan patients. Methods: Participants from the Australian and New Zealand Fontan Registry with dual-energy X-ray absorptiometry scans were included. Appendicular lean mass (ALM), appendicular lean mass index (ALM divided by height squared; ALMI) and total body fat mass percentage (%BF) were calculated. ALMI and %BF z-scores were derived using age- and sex-matched reference ranges. The primary outcome was Fontan failure (death, transplantation, New York Heart Association functional class III/IV, protein-losing enteropathy, and plastic bronchitis) or moderate-or-severe ventricular dysfunction. Results: 144 patients were included. Mean %BF was 29% (SD 10) with 50% having increased adiposity. Mean ALMI z-score was −1.4 (SD 1.1); one third of patients had skeletal muscle deficiency (ALMI z-score < −1 and −2) and another third had Fontan-associated myopaenia (ALMI z-score < −2). Age and %BF were associated with the risk of the endpoint in univariable regression (age: HR 1.09 per year, 95% CI 1.02–1.17, p = 0.01; %BF: HR 1.08, 95% CI 1.01–1.17, p  = 0.03). On multivariable regression, every 1% increase in %BF was associated with a 10% increased risk of reaching the clinical endpoint (HR 1.10, 95% CI 1.01–1.19; p  = 0.03). ALM was not associated with the endpoint (HR 1.02 per kg, 95% CI 0.88–1.20, p  = 0.77). Conclusions: Increased adiposity is associated with higher risk for adverse outcomes. Prospective studies to assess lifestyle interventions to optimise body composition should be prioritised. Highlights: Increased adiposity and decreased lean mass are common in Fontan patients Increased adiposity is associated with adverse clinical outcomes in this population Optimising body composition should be a focus of care for these patients